Students' Reactions Toward Teaching Listening Through Discovery Learning Using Podcast - Revastia, Rizky (PROJECT (Professional Journal of English Education), 2025)
In Listening, listeners are expected to comprehend what others are saying and to respond appropriately, so implicitly authorizing the use of new and suitable language in capturing the meaning of what they hear. The goal of this research is to acquire a better understanding of students' impressions of listening instruction through exploration learning via podcasts. The participants of this study were 20 eighth-grade pupils at a junior high school. Based on the data collected from twenty students and ten closed questions, it can be determined that the majority of students had a favorable view of the use of Podcasts in learning to listen to Invitation. The results indicated that virtually all students agreed that the implemented learning increased their desire to participate in learning and increased their drive to attain excellent grades, even though some did not.